The Fuel Properties Of Pyrolytic Oils Derived From Carbonaceous Solid Wastes In Bangladesh (Jurnal Teknologi (Sciences & Engineering), 2012)
The carbonaceous solid wastes in the form of rice-straw, jute-stick and bagasse were pyrolyzed in a fluidized bed reactor. The condensed oils were analyzed for their properties as fuels and compared with other biomass derived pyrolytic oils and refined petroleum products. The fuel properties compared were physical properties, calorific value, elemental (CHNOS) analysis and chemical composition using Fourier Transform InfraRed (FTIR) spectroscopy. The results showed that the pyrolysis of biomass may be a potential source of liquid hydrocarbon fuel. Key words: Biomass; pyrolytic oils; fuels properties; CHNOS; FTIR